Demand for Malaysian higher education among ASEAN countries: an income classification based analysis - Suriyani Muhamad,; Fadli Fizari Abu Hassan Asari,; Mahyudin Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2019)
In 2009, Malaysia was ranked as the world’s 11th higher education exporter. However, only 2% of international students enrolled in Malaysia for the same year. In addressing the problem, this research proposes an analysis of Malaysia’s higher education demand from a macro perspective. This is important in getting a holistic view on the international demand for the country’s higher education industry, as well as complementing existing micro-researches which specialize in individual demand. All importers (ASEAN countries) have been classified based on the World Bank’s income classification, namely low-income, lower-middle-income, upper-middle-income and high-income. Three variables namely per capita income, consumer price index and physical distance are used in describing the demand. The findings of the study prove that different income classification results in different demand. The identification of high-potential importing countries is essential in achieving a total of 200,000 international enrolments by 2020, as outlined in the Malaysia economic transformation program.